СТРУКТУРНАЯ РЕАЛИЗАЦИЯ ДВУХКОНТУРНЫХ КОРРЕКТОРОВ КОЭФФИЦИЕНТА МОЩНОСТИ НА ОСНОВЕ КВАЗИРЕЗОНАНСНЫХ ИМПУЛЬСНЫХ ПРЕОБРАЗОВАТЕЛЕЙ, ПЕРЕКЛЮЧАЕМЫХ ПРИ НУЛЕВОМ ТОКЕ - Денисов, Ю.А.; Степенко, С.А. (Інститут електродинаміки НАН України, Київ, 2015)
This article is devoted to the development of active power factor corrector based on the parallel quasi-resonant pulse converter with zero current switching of the power transistor. The features of the structural realization of the converter control system have been considered by analyzing of steady-state current static errors for different possible structures. In contrast to the power factor correctors with voltage loop as the main, where the process of finite duration is set for five cycles, in the power factor corrector with current loop as the main it is set for three cycles. It was shown, that high-frequency two-loops active power factor correctors based on the parallel quasi-resonant pulse converter with zero current switching is advisable to carry out with current loop as the main, in which the regulator must ensure the implementation of processes of finite duration. References 15, table 1, figures 4.